Conformational and structural analysis of 2-allyl-1,2-benzisothiazol-3(2H)-one 1,1-dioxide as probed by matrix-isolation spectroscopy and quantum chemical calculations - Gómez-Zavaglia, A. (2014)
2-Allyl-1,2-benzisothiazol-3(2H)-one 1,1-dioxide (ABIOD) has been studied by matrix-isolation infrared spectroscopy and quantum chemical calculations. A conformational search on the B3LYP/6-311++G(3df,3pd) potential energy surface of the molecule demonstrated the existence of three conformers, Sk, Sk0 and C, with similar energies, differing in the orientation of the allyl group. The calculations predicted the Sk form as the most stable in the gaseous phase, whereas the Sk0 and C conformers have calculated relative energies of ca. 0.6 and 0.8–3.0 kJ mol 1, respectively (depending on the level of theory). In agreement with the relatively large (>6 kJ mol 1) calculated barriers for conformational interconversion, the three conformers could be efficiently trapped in an argon matrix at 10 K, the experimental infrared spectrum of the as-deposited matrix fitting well the simulated spectrum built from the calculated spectra for individual conformers scaled by their predicted populations at the temperature of the vapour of the compound prior to matrix deposition. Upon annealing the matrix at 24 K, however, both Sk and Sk0 conformers were found to convert to the more polar C conformer, indicating that this latter form becomes the most stable ABIOD conformer in the argon matrix.